Metanephric adenoma in a pediatric patient case report - Kamış, Şule Çalışkan; Yağcı, Begül; Koç, Ayşe Selcan; Taş, Zeynel Abidin (Frontiers in Pediatrics, 2025)
Metanephric adenoma (MA) is a rare benign renal tumor, with an incidence of 0.2%–1%. Approximately 90% of MA cases present with the BRAF V600E mutation. This study reports an 8-year-old male child who presented with abdominal pain for one month. Abdominal ultrasound revealed a cystic necrotic mass measuring 56 × 45 mm in the right kidney. A preliminary diagnosis of Wilms tumor (WT) led to the initiation of preoperative vincristine therapy. Right nephroureterectomy was performed by pediatric surgery. Histopathological analysis could not differentiate between MA and WT. Immunohistochemical findings were positive for WT1, PANCK (weak focal), INI1 (intact), PAX8, CD56, and CD57. Genetic testing confirmed the presence of the BRAF V600E mutation (1799T > A, 1799_1800TG > AA). The patient was diagnosed with MA and was followed without chemotherapy. In conclusion, MA, which can be mistaken for WT, should be considered in the differential diagnosis of pediatric renal neoplasms. Immunohistochemical evaluation and genetic testing are essential for a definitive diagnosis.